Treatment of generalized infantile myofibromatosis with sorafenib and imatinib: A case report. Issue 6 (19th April 2020) - Bidadi, Behzad; Watson, Andrea; Weigel, Brenda; Oliveira, Andre; Kirkham, Justin; Arndt, Carola
Abstract: Infantile myofibromatosis (IM) is characterized by solitary musculoskeletal nodules presenting during infancy but can manifest as multiple lesions with visceral involvement. Multicentric IM with visceral involvement carries a high risk of mortality and there is no consensus on treatment. We present a case of a patient with multicentric IM and pulmonary involvement who progressed on several chemotherapeutic regimens and subsequently had a complete response to sorafenib and later imatinib. This report describes the novel use of sorafenib and imatinib to treat generalized IM and the role of continued tyrosine kinase inhibitor therapy to maintain remission.